Editorial Introduction - Catherine Compton-Lilly (Networks: An Online Journal for Teacher Research, 2006)
Gordon Wells is the founder of Networks and has served as our editor for eight volumes (AKA eight years). He has kindly agreed to continue to serve to the review board and continue to act as a mentor to myself as I take on the new responsibility of editing this online journal. The transition has taken some time, much more time than I had hoped, but I suspect that the time was well invested. With a lot of help from a phenomenal group of people here at the University of Wisconsin Madison, we have been able to use the Open Journal System to post the journal and to handle the submission process. This system is a extremely helpful in handling submissions and tracking those submissions through the review process. It is with great humility that I commence my tenure as editor. I suspect our readers will find this current issue of Networks to be engaging and informative.